Exploring the impact of virtual reality experience, interactivity, engagement, and content quality on user experience and rebooking intention in Saudi Arabian hotels - Fait, Adil Mohamed Ahmed (Edelweiss Applied Science and Technology, 2025)
The increasing digital transformation influences the hospitality industry by reshaping the way of service experience and evaluation through experiential and interactive technologies. Yet, little empirical evidence has been found that studies how these digital attributes jointly influence consumer experience and behavioral loyalty in developing markets like Saudi Arabia. This research investigates the impacts of Virtual Reality Experience (VRE), Interactivity (INT), Engagement (ENG), and Content Quality (CQ) on User Experience (UE), and how UE predicts Rebooking Intention (RB) in Saudi hotels. A quantitative, cross-sectional design was used based on responses from 466 digitally active hotel customers. SEM with AMOS tested measurement and structural models via Confirmatory Factor Analysis (CFA) and model fit indices: χ²/df, CFI, TLI, RMSEA, SRMR. Interactivity, Engagement, and Content Quality significantly enhanced User Experience, whereas Virtual Reality Experience did not show any direct effect. User experience strongly predicted Rebooking Intention. The findings indicate that emotionally engaging, interactive, and content-rich environments outperform technological novelty. This study has advanced the S-O-R and Service-Dominant Logic frameworks, providing insights into user-centered digital hospitality strategies aligned with Saudi Vision 2030.